An Analysis of Metaphor in Batak Toba Song Lyrics (Mother Love’s Theme) - Doris Yolanda Saragih (Budapest International Research and Critics University, 2021)
The aims of this research are to classify Metaphors in Batak Toba Song Lyrics (Mother's Love Theme).This research used Kovecse’s theory (2010) said that there are three types of Metaphor: Structural Metaphors, Ontological Metaphors, and Orientational Metaphors. The method in this research applied qualitative method. The data were collected by downloading eight collection of Batak Toba Song Lyrics (Mother's Love Theme), listening them, transcribing them in English Language, identifying and putting them into table.The data were also analyzed by analyzing the data, classifying the data, deciding the research findings, and drawing the conclusion. The result in this research, there are 21 the data found in eight collection of Batak Toba Song Lyrics (Mother's Love Theme), namely 5 structural (23, 80%), 10 ontological (47,61%), and 6 orientational (28,57%). Therefore, a number of selected Bataknese songs were dominated by ontological metaphor